Perbandingan Dua Observer Kecepatan Motor Arus Searah pada Sistem Kendali tanpa Sensor Kecepatan - Bernadeta Wuri Harini; Martanto; Tjendro (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
In a sensorless motor speed control system, the motor speed is not directly measured using a speed sensor, but it is estimated using an observer. The sensorless speed control systems are mostly applied to AC motors, while they have not been widely applied to DC motors. Therefore, this paper presents simple observers to estimate the DC motor speed. The observers used were based on the DC motor electric equation. Two methods were used in this research. The first method was the observer estimating the speed based on the resistance inductance values (L-R method), while the second was the observer estimating the motor’s speed only based on the motor’s resistance value (R method). The speed was estimated using armature current (ia) and voltage (va). Therefore, a current and voltage sensor was used. Not only was the observer estimated, but it was also implemented on a real DC motor. An Arduino microcontroller was used to calculate the speed. The LN298 was used as a DC motor drive. Even though the R method is simpler, the test result showed that its speed estimation was less precise than the L-R method. By manual calculation, the motor speed estimation result in the L-R method had an error of 0.14%, while the motor speed estimation results in the R method had an error of 5.03%. The estimation results of motor speed implemented on a real DC motor and microcontroller system in the L-R method had an error of 3.98%, while the result of the estimation of motor speed in the R method had an error of 4.87%.